A Dynamic Panel Study of Economic Development and the Electricity Consumption-Growth Nexus - Apergis, Nicholas; Payne, J. (Elsevier, 2011)
This study examines the relationship between electricity consumption and economic growth for 88 countries categorized into four panels based on the World Bank income classification (high, upper middle, lower middle, and low income) within a multivariate panel framework over the period 1990–2006. The Larsson et al. (2001) panel cointegration test indicates there is a long-run equilibrium relationship between real GDP, coal consumption, real gross fixed capital formation, and the labor force for the high, upper middle, and lower middle income country panels. The results from the panel vector error correction models reveal (1) bidirectional causality between electricity consumption and economic growth in both the short- and long-run for the high income and upper-middle income country panels; (2) unidirectional causality from electricity consumption to economic growth in the short-run, but bidirectional causality in the long-run for the lower-middle income country panel; and (3) unidirectional causality from electricity consumption to economic growth for the low income country panel.